Manifestaciones de violencia contra la mujer en zonas urbanas y rurales del Perú. - Barja-Ore, J. (2022)
Introduction: Violence against women is a widespread social problem throughout the world, which can manifest in various ways depending on the context of the woman. Objective: To compare the manifestations of violence against women, in urban and rural areas of Peru. Methods: Observational, descriptive and cross-sectional study carried out with the databases of the 2019 Demographic and Family Health Survey. The records of 21518 women of reproductive age were analyzed; weighted and unweighted frequencies were estimated, and the chi-square test (χ2) was applied. Results: The prevalence of violence against women was 57.7%. In psychological violence, it was found that the partner incites jealousy or annoys the woman (36.4%), humiliated her in front of other people (18.5%) and threatened to leave home / take away her children or help economic (16.3%) were more frequent in urban areas (p< 0.001). In physical violence, partner hitting with a fist or another object (17.3%) and kicking or dragging (11.9%) was higher in rural areas (p< 0.001). In sexual violence, 7.2% and 6% of women in rural and urban areas, respectively, were forced to have sexual relations (p= 0.049). Conclusions: Violence against women is more frequent in urban than in rural areas.